2021
DOI: 10.1177/00957984211021229
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Coping in the Relationship Between Endorsement of the Strong Black Woman Schema and Depressive Symptoms Among Black Women

Abstract: The Strong Black Woman (SBW) schema has been consistently linked to negative mental health outcomes among Black women. However, few have begun to explicate the mechanisms by which the endorsement of the SBW schema may influence mental health outcomes. Accordingly, the current study examined coping styles (social support, disengagement, spirituality, and problem-oriented/engagement) as mediators in the association between endorsement of the SBW schema and depressive symptoms in a sample of Black women. Data fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 25 publications
4
13
1
Order By: Relevance
“…The construct is more nuanced than previously thought. For instance, several recent studies linked SBW exclusively to negative outcomes such as depression (see, e.g., Jones et al, 2021; Liao et al, 2020), while the current study found the three components of the stereotype—Mask of Strength, Self-Reliance, and Caretaking—functioned differently in their relation to actual help-seeking and intention to seek help. While SBW self-endorsement overall did not significantly predict actual help-seeking or intention to seek help, post-hoc analyses indicated higher endorsement of the Caretaking subscale related to greater actual help-seeking and higher endorsement of the Mask of Strength subscale related to less actual help-seeking and intention to seek help.…”
Section: Discussioncontrasting
confidence: 61%
“…The construct is more nuanced than previously thought. For instance, several recent studies linked SBW exclusively to negative outcomes such as depression (see, e.g., Jones et al, 2021; Liao et al, 2020), while the current study found the three components of the stereotype—Mask of Strength, Self-Reliance, and Caretaking—functioned differently in their relation to actual help-seeking and intention to seek help. While SBW self-endorsement overall did not significantly predict actual help-seeking or intention to seek help, post-hoc analyses indicated higher endorsement of the Caretaking subscale related to greater actual help-seeking and higher endorsement of the Mask of Strength subscale related to less actual help-seeking and intention to seek help.…”
Section: Discussioncontrasting
confidence: 61%
“…Second, several psychological factors have been found to mediate connections from SBW endorsement to Black U.S. women's mental health, including decreased perceived emotional support, a disengagement coping style (i.e., attempts to distance oneself from the stressor), and self-silencing (Abrams et al, 2019;Jones, Hill-Jarrett, et al, 2021;Watson-Singleton, 2017). In a complex mediation analyses, Liao et al (2020) tested each of the following as direct or serial mediators of the link between SBW and mental health (depressive symptoms, anxiety symptoms, loneliness):…”
Section: Moderators and Mediatorsmentioning
confidence: 99%
“…Many quantitative studies report SBW is negatively related to well‐being and coping behaviors (Jones, Hill‐Jarrett, et al., 2021; Liao et al., 2020; Nelson et al., 2022). However, the qualitative work on SBW and mental health is mixed.…”
Section: Impacts Of the Sbw On Black Womenmentioning
confidence: 99%
See 1 more Smart Citation
“…From the year 1619 (Hannah- Jones, et al, 2021;Olusoga, 2016) to 1783, African chattel slavery had been operating in "America" under British Rule for the first 164 years 14 , during a time when the English dominated the African slave trade. Throughout that period, my British ancestor's progeny largely participated in politics, government, military, and agriculturein the New World; and, they also participated in the horrific and inhumane practices of African chattel slavery, as evidenced by their slave schedules, against my African and Indigenous ancestors, for centuries across multiple generations.…”
Section: Researcher's Ancestral Connections To the Us And Ukmentioning
confidence: 99%